Revisiting the Dickensian echo of the HBO TV series The Wire - Ruano San Segundo, Pablo (International Journal of English Studies, 2019)
This article analyzes the alleged Dickensian echo of the highly-acclaimed HBO TV series The Wire. Charles Dickens is probably the literary author to whom the series has most frequently been likened. This correspondence is scrutinized here, as it seems to have been built upon impressionistic references, rather than on methodical intertextual analyses of both the series and the Victorian author. The analysis is intended to throw new light on the Dickensian ambience of The Wire, which seems to be different than previous critical appreciations of the series have suggested.